SYSTEM OF PREVOCATIONAL REHABILITATION IN THE CZECH REPUBLIC - Svestkova, Olga; Sladkova, Petra (European Scientific Journal, ESJ, 2015)
Prevocational rehabilitation is performed by members of the rehabilitation team to get a functional assessment of the psychosensomotor potential for employment purposes for people with disabilities (patients/clients). Standard methodologies were divided into basic, recommended and special methods for determining the psychosensomotor potential for empolyement. The functional basic methodologies include: Barthel Index, Instrumental routine daily activities test, Daily structure, Interest questionnaire, Self-assessment of pain, Sensory examination, Work curve by Emil Kraepelin and Richard Pauli, Jebsen-Taylor Test, PurduePegboard test - model 320 20, Jamar Dynamometer, Isernhagen Work System, Loewenstein Occupational Therapy Cognitive Assessment, Activity Matching Ability System, WHO DAS II. The recommended methodologies include examinations by experts that each facility is obliged to ensure, if necessary, for example, targeted and comprehensive assessment, spiroergometry, speech examination, psychological, psychiatric examination, hearing examination, visual examination. Special methodologies are according specialization of rehabilitation facilities. Our Department of Rehabilitation Medicine is focused on patients with brain damage, therefore we use Rivermead Behaviour Memory Test, Mini Mental State Examination , The Middlesex Elderly Assessment of Mental State, Prevocational assessment according to Jacobs, Canadian model of employment, General office test Functional, Independence Measure etc. The prevocational evaluation result is sending to Labour Offices and should not contain any confidential medical information. This report may contain recommendations for further education or retraining. Physician completes the discharge paper and he summarizes the evaluation of the rehabilitation team members. This report includes positive employment recommendations and work restrictions.